A segunda lei da termodinâmica e o conceito de entropia: uma proposta de sequência didática potencialmente significativa - Moura, Tiago Martins (2017)
The second law of thermodynamics is closely linked to the concept of entropy, consisting of a list of the most fundamental laws of physics. However, as shown by a systematic review of in the main physics teaching journals of the country, a database of master's dissertations in Physics Teaching at universities consolidated in this area, and textbooks commonly used in public schools in the city of Mossoró/RN, there is, in basic education, a significant lack of works that contemplate didactic interventions in the classroom on these themes. In the present work, carried out within the National Professional Masters in Physics Teaching (NPMPT) program at the Federal Rural University of the Semi-Arid (FRUSA) campus, we present a didactic sequence on these themes. Its implementation took place in nocturnal B1 block, in the unit equivalent to the second year, at the Professor Alfredo Simonetti Center for Youth and Adult Education (CYAE) state school. The didactic sequence was designed to develop contextualized, potentially meaningful learning situations, exploring the interaction between students and between students and teacher, critical and reflexive thinking not being favored in traditional teaching. To this end, we adopted theoretical references present in texts by David Paul Ausubel, Joseph Donald Novak, Paulo Reglus Neves Freire, Marco Antonio Moreira and National Curricular Parameters. A text was prepared, designed as a guide for the development of the didactic sequence, which was complemented, during its implementation, by the creation of learning situations. The sequence is composed of ten lessons, including contents such as: heat engines and their principles of operation, elements of History and Philosophy of Science (HPS) and Science, technology, society and environment (STSE), the Carnot cycle, the second law of thermodynamics, entropy in isolated systems (reversible and irreversible processes), statistical interpretation of entropy, entropy in living systems, thermodynamic temperature entropy-TS plots, and calculation of the amount of heat in technological processes. The results of the activities developed and the application of the post-test showed that the strategies used in the didactic sequence were effective since the verified results were better when compared to the pre-test results.